Parameters affecting the mechanical digging of peanut crops from three different shaped plots - Borba, Matheus Anaan de Paula [UNESP]; da Silva, Rouverson Pereira [UNESP]; dos Santos, Adão Felipe [UNESP]; Damasceno, André Ferreira [UNESP]; Zerbato, Cristiano [UNESP] (Southern Cross Publishing, 2018)
The mechanical harvesting efficiency of agricultural crops affects operational quality and production costs while being dependent on plot shape, operation planning, and management. Therefore, this study evaluated the operational performance of a mechanical tractor-digger set in the digging of peanut crops planted in different shaped plots. The three trapezoidal, triangular and irregular shaped plots had linear lengths of 812 m (P1), 322 m (P2) and 248 m (P3), respectively. The parameters, effective and operational field capacities; digging and management efficiencies; maneuvering and machine downtimes, including the operator personal needs and displacement in the tracks were determined and used to obtain operational efficiency. The yield of the experimental rural area, in Barrinha, SP, is 3200 kg of peanut ha-1. The experimental design followed the assumptions of statistical process control, and individual value control charts were plotted for each studied variable. The digging operation was monitored and divided into machine downtime, operational time, maneuvering time, and total time. These parameters were then used to calculate the operational capacities and efficiencies of the harvesting operation. It is concluded that plot size and shape affect the operational capacity. Effective and operational capacities are higher in longer plots, lengthwise, while maneuvering times are also shorter. Shorter plots result in digging efficiency losses. Give the best or optimal condition based on results.
Keywords: Arachis hypogaea; Control charts; Mechanized harvest; Operational performance; Statistical process control